Does Serum Zinc Level Affect Severity of Acute Gastroenteritis Among Pre-School Thai Children? - Wongteerasut A; Pranweerapaibul W (Dove Medical Press, 2021)
Anundorn Wongteerasut, Waewploy Pranweerapaibul Division of Gastroenterology and Hepatology, Department of Pediatrics, Phramongkutklao Hospital and Phramongkutklao College of Medicine, Bangkok, ThailandCorrespondence: Anundorn WongteerasutDivision of Gastroenterology and Hepatology, Department of Pediatrics, Phramongkutklao Hospital and Phramongkutklao College of Medicine, 315 Ratchawithi Road, Ratchathewi, Bangkok, 10400, ThailandTel +668 4002 2121Fax +66 2763 9300Email anundorn@gmail.comIntroduction: Acute gastroenteritis (AGE) is a common problem causing significant mortality and morbidity among children. In clinical settings, zinc deficiency leads to diminished resistance to infectious disorders including acute gastroenteritis, especially in the pediatric populations.Purpose: This study aimed to identify the possible effect of body zinc depletion on the severity of acute gastroenteritis among children. The parameters included dehydration status estimated by Modified Vesikari Score (MVS), laboratory findings, amount of intravenous (IV) fluid requirement, need of medications, as well as a clinical course of illness.Materials and Methods: We conducted a prospective observational study with 107 children 3 months to 5 years old with AGE that were admitted to an inpatient unit. A comparison was made between children with normal (≥ 80 μg/dL: n=79 cases) and low serum zinc levels (< 80 μg/dL, n=28 cases).Results: The definite zinc deficiency (< 60 μg/dL) was demonstrated only in 3.7% of cases. The severity of dehydration, classified by MVS, reveals a significantly higher increase in children with low serum zinc levels (12.13 ± 2.4 vs 13.14 ± 1.86 points, p < 0.045). Additionally, the children with low serum zinc levels had a significantly higher number of prolonged vomiting episodes more than 24 hours (42.4% vs 72%, p = 0.013) and three cases of post-gastroenteritis complications, which are prolonged fever and persistent diarrhea, were identified only among patients with low zinc levels (p = 0.003). However, there was no significant difference in IV fluid requirement, a need for medications, as well as the duration of hospitalization between the groups.Conclusion: A significantly higher dehydration score, which was assessed by MVS, was demonstrated in the participants with low serum zinc levels. Furthermore, the number of children with prolonged vomiting as well as the evidence of post-gastroenteritis complications was also significantly higher in this group.Keywords: serum zinc, acute gastroenteritis, Modified Vesikari Score, children